A panoptic view of the South African wealth tax - Asheer Jaywant Ram (South African Journal of Economic and Management Sciences)
Background: Wealth taxes are a topic of intense debate, with most countries having either abolished them or considered, but not implemented such measures. The South African government is contemplating the introduction of a wealth tax, purportedly to enhance revenue collection.